Ultrastructural changes of the astroglia in experimental postresuscitation encephalopathy. - Tertishniy, S. I. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Astroglia plays crucial role in the functioning of the central nervous system both in normal and in pathological conditions. Data concerning changes of the astroglia during postresuscitational brain pathology are reare and fragmentary. Objective. To study morphogenesis of the ultrastructural changes in astrocytes in postresuscitational encephalopathy after experimental clinical death. Methods. Clinical death lasting 6-8 minutes was modeled on 17 domestic cats with subsequent resuscitation. The brain was studied after 1, 3 hours, 1, 3, 6-12, 30 days after the clinical death using optical light microscopy and electron microscopy techniques. Results. During 1 hour of postresuscitative period uneven swelling of mitochondria with the local focal reduction of cristae and matrix in the perikaryon and processes of protoplasmic and fibrous astrocytes occurs. Increased in volume and devastated areas of cytoplasm are observed in astrocytes caused by reduction of free polyribosome and glycogen. The number of satellite glial cells is increased in medium density neurons without serious ischemic-coagulation changes of the nucleus and cytoplasm. The outer membranes of sharply increased astrocytic processes are destroyed in some areas, thereby forming a large cavity of true pericellular edema around lysed ischemically damaged neuron. Three days after piecemeal necrosis are formed. Phagocytic astrocytes are found in the interface with intact tissue. In some astrocytes submicroscopic signs of recovering organelles of partially destroyed cytoplasm are revealed. 3-6 days after experiment in the cerebral cortex significant cytoarchitectonic violations are found. They are caused by mosaic-focal "loss" of lysed neurons, fine-focal proliferation of glial cells in areas of destructing neurons, as well as by a violation of the normal orientation of bodies and processes of ischemic-necrotic nerve cells surrounded by expanded astrocytic processes. In subependimal areas of the lateral ventricles 3-6 days after experiment large foci of proliferating glial cells are revealed. 6-12 days after experiment focal selective neuronal necrosis are transformed in the foci of substitutional astrocytic gliofibrosis. 30 days after experiment fibrous astrocytes are observed adjacent to the damaged myelinated axons in the cortex and white matter, performing simultaneously synthetic and phagocytic function. Conclusion. 1. Destructive, adaptive, reparative and proliferative changes of astroglia develop in the brain after clinical death with certain dynamics within postresuscitative period. 2. Along with the destruction of the glial cells, adaptive changes of surviving astrocytes are enhanced in the early postresuscitative period. They are aimed at metabolic and transport support of partially damaged neurons and maintenance of hydro-ionic balance of the central nervous system. 3. Phagocytic function of astrocytes is activated in the foci of selective neuronal necrosis. In the distant postresuscitation period activated proliferation of astrocytes is followed by the development of substitutional astrocytic gliosis and gliofibrosis.